Tumor Testing for Somatic and Germline BRCA1/BRCA2 Variants in Ovarian Cancer Patients in the Context of Strong Founder Effects - Peixoto, Ana; Pinto, Pedro; Guerra, Joana; Pinheiro, Manuela; Santos, Catarina; Pinto, Carla; Santos, Rui; Escudeiro, Carla; Bartosch, Carla; Canário, Rita; Barbosa, Ana; Gouveia, Alfredo; et al. (Frontiers in Oncology, 2020)
Deleterious variants in the BRCA1/BRCA2 genes and homologous recombination deficiency (HRD) status are considered strong predictors of response to poly (ADP-ribose) polymerase (PARP) inhibitors (PARPi). The introduction of PARPi in clinical practice for the treatment of patients with advanced ovarian cancer imposed changes in the molecular diagnosis of BRCA1/BRCA2 variants. BRCA1/BRCA2 tumor testing by next-generation sequencing (NGS) can detect simultaneously both somatic and germline variants, allowing the identification of more patients with higher likelihood of benefiting from PARPi. Our main goal was to determine the frequency of somatic and germline BRCA1/BRCA2 variants in a series of non-mucinous OC, and to define the best strategy to be implemented in a routine diagnostic setting for the screening of germline/somatic variants in these genes, including the BRCA2 c.156_157insAlu Portuguese founder variant. We observed a frequency of 19.3% of deleterious variants, 13.3% germline, and 5.9% somatic. A higher prevalence of pathogenic variants was observed in patients diagnosed with high-grade serous ovarian cancer (23.2%). Considering the frequencies of the c.3331_3334del and the c.2037delinsCC BRCA1 variants observed in this study (73% of all BRCA1 pathogenic germline variants identified) and the limitations of NGS to detect the BRCA2 c.156_157insAlu variant, it might be cost-effective to test for these founder variants with a specific test prior to tumor screening of the entire coding regions of BRCA1 and BRCA2 by NGS in patients of Portuguese ancestry.